The Role of Project Management Standardization in SMEs: Analyzing the Linkages Between Knowledge Management, Project Management, and Stakeholder Satisfaction - Börsch, Pablo (My University, 2022)
Small and Medium-Sized Enterprises (SMEs) are the backbone of our economies. Today's trend of taking every business activity as a project explains why more and more companies are working on a project basis. Previous research has shown that humans, as well as companies, desire a structured approach to work, avoiding uncoordinated business process activity. Little is known about how the structuring of processes influences SMEs. In order to structure an approach or process, a framework consisting of standards and Best Practices must be established. The role of the framework is to give guidance and improve cross-project efficiencies. Thus, this research study investigates the role of Project Manage-ment Standardization in SMEs. Here, the linkages between standardization and knowledge management (KM), project management (PM), and stakeholder satisfaction in SMEs are analyzed. The theoretical framework integrates the vast literature on the four research topics of stand-ardization, knowledge management, project management, and stakeholder satisfaction into a joint context for SMEs. The analytical part of the research is based on a single-case study of a German SME. Insights are gained from data gathered through six semi-structured inter-views with different experts throughout the company's hierarchy. The research highlights the interconnectedness of the four topics and the central role of project management standardization in SMEs. In order to maintain an efficient PM as the company grows, standardization of processes is inevitable. Standardization requires active KM to obtain explicit knowledge. Hence, standardization and KM are key drivers for sustainable business growth. Additionally, standardization accelerates the company's maturation as the company is moving away from informal, unbureaucratic, and exclusively people-oriented management approaches. Centrally stored and accessible explicit knowledge leads to transparent structures that create clear responsibilities and enhance communication in PM. Consequently, process standardization supports a better ‘estimability’ of the work, reducing uncertain requirements, inadequate documentation, hidden business rules, and requirements creep. This increases the satisfaction of all project stakeholders, making work in the company more efficient and creating a transparent organizational culture.
Keywords: small and medium-sized enterprises; knowledge management; project management; case study; standardisation; projects; processes; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business